Cinética de hidrólisis enzimática del raquis de banano para la producción de azúcares fermentables. - Mendoza Guzman, Giancarlo Steven; Torres Jungal, Carlos Luis (Machala : Universidad Técnica de Machala, 2021)
The continued exploitation of the non-renewable resource (petroleum) as a source of energy continues to threaten society and the environment. For this reason, global research on obtaining bioenergy to minimize and replace non-renewable resources is increasing dramatically. New biotechnologies are multiplying to produce these resources with high added value, great economic viability and very sustainable, offering value for the environment, collective equality and partial substitution of oil. These biotechnologies are carried out thanks to various microorganisms capable of degrading, transforming or hydrolyzing the sugars (monosaccharide - disaccharides - polysaccharides) of the lignocellulosic biomass where we have the skins of fruits and vegetables, organic waste, residues of agricultural processes such as the banana rachis, use this waste as a raw material to produce fermentable sugars followed by a bioconversion to obtain energy sources such as bioethanol, being a renewable resource that integrates a great contribution to sustainable development for countries in order to derive the best use of energy production. The study consisted in determining the kinetics of enzymatic hydrolysis of rachis banana to produce fermentable sugars to apply it to a bioconversion into ethanol by the reuse of agricultural residues. In this case, it is the rachis banana, these sugars are used to generate products with high added value which are experiencing great development, in order to partially replace conventional fuels and to contribute to energy, protection and environmental diversity and to '' apply new energy technologies.
La continua explotación del recurso no renovable (petróleo) como fuentes energéticas siguen amenazando a la sociedad y el ambiente. Por ello las investigaciones globales de obtener bioenergías para minimizar y sustituir los recursos no renovables incrementa notablemente. Las nuevas biotecnologías están en auge para producir estos recursos de alto valor añadido, de gran viabilidad económica y muy sostenible ofreciendo valorar el medio ambiente, igualdad colectiva y una sustitución parcial del petróleo. Estas biotecnologías se logran mediante diversos microorganismos capaces de degradar, transformar o hidrolizar los azúcares (monosacárido – disacáridos – polisacáridos) de biomasa lignocelulósicas donde tenemos cascaras de frutas, vegetales, desechos orgánicos, residuos de los procesos agrícolas como es el raquis de banano, utilizar estos residuos como materia prima para producir azúcares fermentables seguido de una bioconversión para obtener las fuentes energéticas como el bioetanol siendo un recurso renovable que integra un gran aporte al desarrollo sostenible para los países con el fin de aprovechar al máximo la producción energética. El estudio consistió en determinar la cinética de la hidrólisis enzimática del raquis de banano para producir azúcares fermentables para aplicarlo a una bioconversión a etanol mediante la reutilización de residuos agrícola. En este caso, se trata del raquis del banano, estos azúcares son utilizados para generar productos de alto valor añadido que están experimentando un gran desarrollo, con el fin de reemplazar parcialmente los combustibles convencionales y contribuir a la diversidad de la energía, la protección y ambiental y aplicar nuevas tecnologías energéticas.
Keywords: CINETICA; AZUCARES FERMENTABLES; HIDROLISIS ENZIMATICA; RAQUIS DE BANANO